P109 Optimal dosing regimen of caspofungin in children: milligram per kilogram or milligram per square meter?. Issue 6 (17th May 2019) - Yang, X-M; Leroux, S; Storme, T; Zhang, D-L; Adam de Beaumais, T; Shi, H-Y; Yang, Y-L; Wang, X-L; Zhao, W; Jacqz-Aigrain, E
Abstract : Background: Caspofungin is the first echinocandin to be used as a first-line antifungal agent for Candida spp. infections in febrile, neutropenic adult and paediatric patients. To date, the optimal dosing of capofungin in children has not been determined. We evaluated the population pharmacokinetics of caspofungin in children (2–12 years old) and defined an appropriate dose in order to optimize caspofungin treatment in this vulnerable population. Methods: Blood samples were collected from 48 children treated with caspofungin and drug concentrations were quantified by HPLC-MS. Population pharmacokinetic analysis and Monte-Carlo simulation were performed using NONMEM software Results: Data from 48 children was available for population pharmacokinetic analysis. A two-compartment model with first-order elimination had the best fit with the data. Subsequent covariate analysis demonstrated that body surface area had a significant correlation with caspofungin pharmacokinetics compared to body weight. Monte Carlo simulation demonstrated that >90% of a simulated paediatric population (age range, 2–12 years) treated with a loading dose of 70 mg/m 2 followed by a 50 mg/m 2 maintenance dose once daily would reach a minimum inhibitory concentration of 1 µg/mL, the proposed susceptibility breakpoint for caspofungin against Candida spp. Conclusion: The population pharmacokinetics of caspofungin was evaluated and revealed that adjustment of caspofungin based on body surface area is most appropriate for paediatric use. Disclosure(s): Nothing to disclose